Determinants of Social Media Adoption by Large Companies - Bogea,Felipe (Universidad Alberto Hurtado. Facultad de Economía y Negocios, 2018)
Abstract: Social media marketing has become a central issue for companies and marketers. Few studies have, however, specifically researched factors and barriers influencing the adoption of social media at company level. This study addresses this gap by focusing on furthering the theory involved in the adoption social media at company level. Based on the findings of semi-structured in-depth interviews with 17 marketing executives of large companies in Brazil, six variables that weigh in the adoption of social media were identified: the demonstrability of the results, the customers’ presence on Social media, knowledge of social media, stakeholder influence, common sense as related to digital marketing and the executive’s age. Additionally, we propose a theoretical model of social media adoption, in the light of the Technology Acceptance Model (TAM).